2016
DOI: 10.18632/oncotarget.11514
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of transarterial chemoembolization and sorafenib in Chinese patients with unresectable and recurrent hepatocellular carcinoma

Abstract: We explored the hypothesis that sorafenib may improve the effect of transarterial chemoembolization (TACE) in patients with recurrent hepatocellular carcinoma (HCC) and that longer sorafenib duration was associated with additional survival benefits. In this retrospective, nested case-controlled study, 1126 cases of unresectable HCC were collected. Patients with unresectable disease treated with TACE+sorafenib (n=245) and TACE alone (n=245) and those with recurrence after surgery treated with TACE+sorafenib (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 36 publications
1
13
1
Order By: Relevance
“…In previous studies, the baseline characteristics of included population showed a prevalence of HBV of about 90% 55 , 56 and a rate of noncirrhosis ranging from 35.4% to 55.1%. 43 , 45 , 56 , 57 It should be noted that, in some area with high prevalence of HCV infection, such as Japan, the rate of patients with rHCC with HBV is only 19.6% to 20.6%. 58 , 59 This may be because of the differences in terms of the geographical distribution, genetics, ethnicity, and different chronic viral infection in patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the baseline characteristics of included population showed a prevalence of HBV of about 90% 55 , 56 and a rate of noncirrhosis ranging from 35.4% to 55.1%. 43 , 45 , 56 , 57 It should be noted that, in some area with high prevalence of HCV infection, such as Japan, the rate of patients with rHCC with HBV is only 19.6% to 20.6%. 58 , 59 This may be because of the differences in terms of the geographical distribution, genetics, ethnicity, and different chronic viral infection in patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…They can combine iodine oil and gelatin sponge with an embolization of tumor blood vessels which control the slow release of chemotherapy drugs. Therefore, the tumor tissue will have hypoxia, necrosis and apoptosis ( 15 ). The median survival period will increase at least 5.0–8.0 months ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the elevated levels of VEGF and other angiogenic factors secreted by the hypoxic tumor cells after TACE has the role of promoting abnormal angiogenesis [ 11 ]. Indeed, by targeting VEGF, platelet derived growth factor receptor, and other signaling, anti-angiogenesis agents proved to block tumor development and neo-angiogenesis [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%